ANALISIS IKLIM KESELAMATAN KERJA DI PT. XYZ BALIKPAPAN 2021 - Deni Eri Zulfirman; ZULKIFLI DJUNAIDI (Universitas Pahlawan, 2021)
This study was conducted to determine the safety climate, the safety climate reflects workers' perceptions of the true value of safety in an organization - as a contributing factor to the reduction of accidents due to accidents. The purpose of this study was to determine the level of health and safety scores in the company. This study uses a descriptive analytical method with a total of 100 respondents (total respondents) with a variable measuring the level of work safety using a questionnaire published by the National Research Center for the Danish work environment, namely the Nordic Climate Safety Questionnaire 50 (NOSACQ-50) which contains 50 statements and has been completed. tested and translated in 40 languages, one of which is Indonesian. This research was conducted at PT. XYZ Balikpapan which starts in January until March 2021,. The results of this study indicate that there are 3 dimensions that have an average value below 3.30, namely the management safety empowerment dimension, management safety justice dimension and worker’s safety priority and risk non-acceptance dimension. Suggested improvements include making decisions and receiving advice and input from workers regarding work safety and being fair to workers regarding occupational safety and health for management and prioritizing work safety and not taking risks even though the work is busy and reducing risk-taking behavior that is dangerous for workers.